Method and results of studying the influence of grinder knife parameters on specific work of feed cutting - Ayugin Nikolay (EDP Sciences, 2021)
To study the process of feed cutting of vegetable origin, a laboratory setup based on the principle of an impact machine, which made it possible to provide a cutting speed in a sufficiently wide range, was developed at Ulyanovsk State Agrarian University. To ensure the required sliding angle, the cutting element (knife) has an adjusting plate with a lock, which allows changing the sliding angle in the range from 0 to 70 degrees. A laboratory setup can be used to study the cutting process of various feeds used in animal husbandry. The analysis of the most important parameters affecting the specific work of feed cutting was carried out, the dependence of the influence of the grinder knife design parameters (blade thickness and sliding angle) on specific cutting work of straw, potatoes, feed beetroot, carrots, corn cobs, stalks and leaves was established. The results of the laboratory studies indicate that at certain (appropriate) values of the knife sliding angle of the grinder, it is possible to achieve a decrease of specific cutting work of some feed (corn cobs and stalks, potatoes, feed beetroot, carrots) by 25 … 37%, when cutting corn leaves – by 15% , wheat straw – by 3%. This dependence is typical of a wide range of cutting speeds of the materials under study (from 2 to 10 m / s), the differences fit into the measurement inaccuracy. The results of the laboratory studies and the presented method can be used for design development of grinder cutting device for livestock enterprises.